ANALISIS KELAYAKAN USAHA PENGOLAHAN SELAI NANGKA DITINJAU DARI JENIS DAN KONSENTRASI BAHAN PEMBENTUK GEL - Samsuri Tirtosastro; Sakunda Anggarini (Universitas Tribhuwana Tunggadewi, 2007)
The aims of this research were to elucidate the best concentration of gelling agents (carragenans, pectins, agaroses) for producing jackfruit jams with best chemical, physical and organoleptical characteristics, and the financial aspects of the best jackfruit jam production. Six treatments of gelling agents addition of 0.5% and 0.6% agaroses; 0.3% and 0.5% pectins and 0.2% and 0.3% carragenans, were arranged in a randomized block design with three replicates. Analysis factors were performed for water content, texture, pH, syneresis and capability of performance and also organoleptics i.e. colours, texture and flavours. Results of this research showed that addition of 0.3% pectins produced best quality of jackfruits jams